Measurement of effective activity concentration of natural radionuclides insitu for assessment of ambient dose equivalent rate in urban environments - V. P. Ramzaev; A. N. Barkovsky (Радиационная гигиена)
At present, the dose rate of gamma radiation from technogenic radionuclides in the territories contaminated as a result of the Chernobyl accident has significantly decreased and, in many cases, is comparable to the dose rate of gamma radiation from natural radionuclides. Therefore, when assessing the external doses to the population at these territories, it is important to correctly evaluate the contribution of natural radiation. The use of field gamma spectrometry (in situ measurements) allows solving this task directly on site without collection of environmental samples and subsequent analytical procedures in laboratory. For the in situ measurements, it is most convenient to use the gamma spectrometers that simultaneously measure both the dose rate in air and the effective activity concentration of natural radionuclides (226Ra, 232Th and 40K). The latter value is unambiguously related to the dose rate of gamma radiation from natural radionuclides when measurements are carried out in the 2π geometry. The possibility of using the results of measuring the effective activity concentration in conditions different from the 2π geometry, in particular, in an urban environment, requires justification. The aim of the study was to empirically determine the relationship between the ambient dose equivalent rate from natural radionuclides and the effective activity concentration of natural radionuclides in typical urban locations. Materials and methods. Simultaneous measurements (n = 170) of the total ambient dose equivalent rate and effective activity concentration were performed in the city of St. Petersburg (Russia) in the spring-autumn period in 2017–2024 using a portable gamma spectrometerdosimeter. The device was placed in a backpack on the operator's back. Main results. Based on results of the in situ measurements, the conversion coefficient from effective activity concentration to ambient dose equivalent rate ((nSv/h)/(Bq/kg)) was calculated. The mean ± standard deviation value of the conversion coefficient for the location “street”, “courtyard”, “square”, “embankment”, “bridge”, “park-lawn”, and “park-footpath” was 0.55 ± 0.02 (n = 70), 0.55 ± 0.01 (11), 0.55 ± 0.02 (10), 0.54 ± 0.01 (9), 0.54 ± 0.04 (16), 0.57 ± 0.02 (27), and 0.54 ± 0.01 (27), respectively. Conclusion. The obtained values of the conversion coefficient can be used when performing walk surveys of urban areas to determine contribution of natural sources to the total dose rate of gamma radiation in the case of radioactive contamination of the environment.